2019
DOI: 10.1016/j.tranpol.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of potential autonomous vehicles users according to propensity to use individual versus shared vehicles

Abstract: As the widespread use of autonomous vehicles (AVs) becomes increasingly likely, an important consideration is the extent to which individuals prefer either private ownership or shared use modes. Both modes are currently evolving, each with distinct but overlapping challenges. Understanding the preferences of different population segments can provide insights into where to focus initial efforts to attract individuals into the market, especially in terms of promoting the uptake of shared AVs to optimise the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…In fact, Bösch et al (2018a) and Pakusch et al (2018) affirm that private cars will continue to exist. Although Pettigrew et al (2019) conclude high interest for SAVs in Australia, 29% of the survey participants are found to be non-adopters of any kind of autonomous vehicle. Based on consumer adoption rules and using a market dissemination model called ECAN (Exclusivity, Choice, Access and Need), Grush & Niles (2018) affirm the dominance of private vehicles for next 30 years.…”
Section: Sav Penetrationmentioning
confidence: 96%
“…In fact, Bösch et al (2018a) and Pakusch et al (2018) affirm that private cars will continue to exist. Although Pettigrew et al (2019) conclude high interest for SAVs in Australia, 29% of the survey participants are found to be non-adopters of any kind of autonomous vehicle. Based on consumer adoption rules and using a market dissemination model called ECAN (Exclusivity, Choice, Access and Need), Grush & Niles (2018) affirm the dominance of private vehicles for next 30 years.…”
Section: Sav Penetrationmentioning
confidence: 96%
“…Fourth, in order to enhance technology savviness, policy makers, manufacturers and public transport companies should develop strategies to identify the segments who are more amenable to adoption (Pettigrew, Dana, and Norman 2019). Opportunities for trial should be offered to increase the visibility of usage (Pettigrew, Dana, and Norman 2019).…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…A primary issue identified by the interviewees was the need to make decisions about the infrastructure requirements of transport systems featuring AVs to encourage optimal use of active transport options. The view of many interviewees that ride-sharing models of AV use have the potential to reduce rates of private car ownership are supported by analyses of consumer responses to traditional (i.e., non-autonomous) ride- and car-sharing services (e.g., Uber) on car ownership levels ( Liao et al, 2020 ; Schmidt, 2020 ; Ward et al, 2019 ) and modeling of the anticipated further effects once ride-sharing services are available in autonomous mode ( Pettigrew et al, 2019c ). Research investigating the benefits of providing cycling infrastructure in the pre-AV environment has found that improved facilities can increase participation rates in a highly cost-effective manner ( Aldred et al, 2018 ; Goodman et al, 2013 , Goodman et al, 2014 ; Keall et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%